INSTITUTIONAL MECHANISMS FOR DEVELOPING REGIONAL ECONOMIC POTENTIAL: PANEL DATA EVIDENCE FROM UZBEKISTAN’S SUBNATIONAL ECONOMIES (Scientific Journal of Actuarial Finance and Accounting, 2026)
This study investigates the role of institutional mechanisms in shaping regional economic potential across Uzbekistan’s fourteen administrative regions over the period 2015–2023. The research addresses a critical gap in the empirical literature concerning how institutional quality, governance structures, and regulatory frameworks influence subnational economic performance in transition economies. Employing a panel data methodology encompassing fixed effects, random effects, and system generalized method of moments (GMM) estimators, the analysis draws upon a comprehensive dataset compiled from official statistical records, World Bank governance indicators, and institutional capacity assessments. The findings reveal that institutional quality, measured through composite indices of regulatory efficiency, property rights enforcement, and administrative transparency, exerts a statistically significant and economically meaningful effect on regional economic potential. Specifically, a one-standard-deviation improvement in institutional quality is associated with a 12.4 percent increase in regional gross product per capita. The system GMM results confirm the persistence of regional economic disparities and underscore the endogeneity of institutional arrangements. Furthermore, the analysis identifies heterogeneous effects across regions, with lagging territories demonstrating greater sensitivity to institutional reforms. The study contributes to the growing body of literature on institutions and subnational development by providing granular evidence from Central Asia and offers targeted policy recommendations for institutional capacity building at the regional level.